Pengaruh Ibadat Pagi Harian terhadap Pertumbuhan Iman Mahasiswa STP Dian Mandala Gunungsitoli Tahun 2025 - Martina Rosmaulina Marbun; Clara Srirahayu Lafau (Journal New Light, 2026)
Daily worship is an important tool and spiritual activity that can shape the faith of Catholic students. Because through prayer, liturgy, and service, students are increasingly strengthened in church life and guided to carry out concrete services. Daily worship, such as personal prayer and communal prayer, plays a role in helping students grow in faith and live according to Christian values. Although morning worship is expected to have a positive influence on students, in reality, there are still students who do not attend morning worship regularly. Therefore, this study was conducted to examine the extent to which daily morning worship influences the growth of faith of STP Dian Mandala students. The research method used is qualitative research because this study aims to explore and understand in depth the influence of daily morning worship on the phenomenon of student faith growth, by collecting reading sources, journals, and books to serve as references in writing this scientific paper.